Smart MPPT Solar Monitoring & Load Balancing - Farheen Saba,; Hemendra Khedekar,; Manisha Gaur, (International Journal of Engineering and Management Research, 2024)
Nowadays the most advance solar charge controller available in the market is Maximum Power Point Tracking (MPPT). The MPPT controller is more sophisticated and more expensive. It has several advantages over the earlier charge controller. It is 30 to 40 % more efficient at low temperatures. But making an MPPT charge controller is little bit complex in comparison to the PWM charge controller. This paper presents design, analysis of MPPT charge controller for improving efficiency of the system using Atmega328p.